2010
DOI: 10.1186/1471-2199-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated imidazole derivatives block RNA polymerase II elongation along mitogen inducible genes

Abstract: BackgroundAberrant activation of protein kinases is one of the essential oncogenic driving forces inherent to the process of tumorigenesis. The protein kinase CK2 plays an important role in diverse biological processes, including cell growth and proliferation as well as in the governing and transduction of prosurvival signals. Increased expression of CK2 is a hallmark of some cancers, hence its antiapoptotic properties may be relevant to cancer onset. Thus, the designing and synthesis of the CK2 inhibitors has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…However, several experimental limitations are associated with these conflicting studies. These include the exclusive use of cell models, use of CK2 inhibitors with poor selectivity and high toxicity (Mikula et al 2010), and absence of genetic evidence to demonstrate the specificity of the inhibitors used as well as the differential contribution between CK2α or CK2α’ subunits. We have now confirmed that CK2α’ upregulation in HD is detrimental and contributes to HD onset and progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, several experimental limitations are associated with these conflicting studies. These include the exclusive use of cell models, use of CK2 inhibitors with poor selectivity and high toxicity (Mikula et al 2010), and absence of genetic evidence to demonstrate the specificity of the inhibitors used as well as the differential contribution between CK2α or CK2α’ subunits. We have now confirmed that CK2α’ upregulation in HD is detrimental and contributes to HD onset and progression.…”
Section: Discussionmentioning
confidence: 99%
“…The adenosine analog 5,6-dichloro-1-␤-D-ribofuranosylbenzimidazole (DRB) inhibits the Pol II Ser-2 carboxyl-terminal domain kinase, CDK9, a component of the positive transcription elongation factor (P-TEF-b) (62)(63)(64). We used DRB to explore the role of Pol II elongation on the recruitment of ERK cascade components to the EGR-1 gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin cross-linking and cell harvesting were performed as previously described. 16 Chromatin was sheared for seven rounds of 20 s (1 s pulse, 0.5 s gap) on-off pulses with a 500-Watt Ultrasonic Processor (Cole-Parmer Instrument Co., Vernon Hills, IL, USA) equipped with a microtip and set to 30% of maximum power. Chromatin immunoprecipitation (ChIP) assays were performed using the Matrix-ChIP platform as previously described.…”
Section: Methodsmentioning
confidence: 99%